Réponses

2014-01-12T16:41:08+01:00
Bonjour
(2x+1)² - 1 est une différence  de carrés
donc la forme factorisée est
(2x+1 -1)(2x+1 +1) = 2x(2x +2) donc vrai

A = (4x+5)² - ( 3x -2)²
Développement
(16x² + 40x +25) - ( 9x² - 12x +4)
16x² +40x +25 -9x² +12x -4
7x² + 52x +21

Factorisation
Ici aussi, différence de 2 carrés donc
(4x+5 +3x-2)(4x+5 -3x +2)
(7x +3)(x +7)
Pour x = 1
A = ( 7+3)(1+8)
10 x 9 = 90

pour x = -3/7
A = (-21/7 +3)(-3/7 +7)
(-21/7 + 21/7) ( -3/7 + 49/7)
= 0


Exercice 1 : (2x + 1)² - 1 = (2x)²+1*2x*2+1+1
= 4x²+4x+2 = 2(2x²+2x+1)